Unregistered Marriage and the Legal Impact, A Book Review “Kepastian Hukum Perkawinan Siri dan Permasalahannya” Zainuddin SH MH & Afwan Zanuddin SH MH, Deepublish Yogyajarta, 95 Pages, ISBN: 978-602-435-120-1 - Gufron, Dede Muhammad (Universitas Negeri Semarang, 2021)
This book explains the legal certainty aspects of unregistered marriages in Indonesia. Unregistered marriages have many implications, especially with regard to law, child status, and inheritance. The book